Analisis Mutu Biodiesel Menggunakan Metode Quality Loss Function dan Rancangan Perbaikan di PT. XYZ - Zaharuddin Zaharuddin (Jurnal Optimalisasi, 2020)
PT. XYZ is a company engaged in the processing of palm oil with the concept of production side by side with consumer orders (make to order). Production results do not match the specifications desired by consumers. A total of 19 parameter values of X diglycerides and 17 parameter values of X triglycerides from biodiesel products produced by the company exceed the upper and lower limit values (out of control) so that the cost of repairing biodiesel by the company increases. The loss function between quality assessment between damage and loss is used to assess the direct relationship between loss and damage in the process. By using the Quality Loss Function method of the Smaller the Better type the quality value received by the company is Rp. 16,320,624,192.96.